Study on Critical Damage Width of Parallel Double-Free Surface Blasting - Shi, Jianjun; Miao, Xiaopeng; Meng, Haili; An, Huaming; Zhang, Wei (Frontiers in Earth Science, 2022)
Reserved rock wall is usually used in blasting operation when one side has an important protection object. Dike demolition blasting was essentially a parallel double free surface blasting, blasting is the ideal effect of casting a side fully broken rock mass, throwing, on the other side (protection) side of rock mass at the injury status of "broken and do not come loose, the minimum thickness of the rock wall last could hole to protect the width of side of the free surface, called the critical damage width. Based on the theory of multi-boundary blasting, the relationship among throwing effect, boundary condition and charge quantity of parallel double-free surface blasting is expounded in this paper. The model of equivalent subcharge package was established to deduce the relationship of bilateral resistance lines, and the theoretical value of critical damage width was 2.05W (minimum resistance line).The minimum resistance line with the measured value of critical damage width of 2.5 times was determined by single row and hole by hole initiation field test based on the demolition blasting of rock wall in yangtou Crossing station reconstruction project of Yuhuai double line.The study of critical damage width of parallel double free surface blasting can provide theoretical guidance for similar projects.